A family of potential-density pairs for galactic bars - Dehnen, Walter; Aly, Hossam (Monthly notices of the Royal Astronomical Society, 2023)
Abstract: We present a family of analytical potential-density pairs for barred discs, which can be combined to describe galactic bars in a realistic way, including boxy/peanut components. We illustrate this with two reasonably realistic compound models. Computer code for the evaluation of potential, forces, density, and projected density is freely provided.
Gesehen am 09.05.2023
Advance Access publication 2022 October 29